2017
DOI: 10.1017/s0007485317000724
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-dependent development ofHelicoverpa armigera(Hübner) (Lepidoptera: Noctuidae) and its larval parasitoid,Habrobracon hebetor(Say) (Hymenoptera: Braconidae): implications for species interactions

Abstract: Habrobracon hebetor (Say) is a parasitoid of various Lepidoptera including Helicoverpa armigera (Hübner), a key pest of different crops and vegetables. The development of both H. armigera and H. hebetor were simultaneously evaluated against a wide range of constant temperatures (10, 15, 17.5, 20, 25, 27.5, 30, 35, 37.5 and 40 °C). Helicoverpa armigera completed its development from egg to adult within a temperature range of 17.5-37.5 °C and H. hebetor completed its life cycle from egg to adult within a tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…The larval stages of H. hebetor are very sensitive to temperature. H. hebetor can survive and complete its life cycle within a temperature range of 15–40 °C [75]. The sex ratio of H. hebetor is affected by temperature and exposure time [69].…”
Section: Factors Influencing Host Parasitism and Reproductive Effimentioning
confidence: 99%
“…The larval stages of H. hebetor are very sensitive to temperature. H. hebetor can survive and complete its life cycle within a temperature range of 15–40 °C [75]. The sex ratio of H. hebetor is affected by temperature and exposure time [69].…”
Section: Factors Influencing Host Parasitism and Reproductive Effimentioning
confidence: 99%
“…H. armigera is one of the most destructive polyphagous cosmopolitan insect pest species (Noor-ul-Ane et al 2018). Over recent decades, several pests have developed resistance against various families of synthetic insecticides (Shakeel et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The soil bacterium Bacillus thuringiensis Berliner subsp. The gregarious ectoparasitoid wasp Habrobracon hebetor Say (Hymenoptera: Braconidae) is an effective larval parasitoid of H. armigera (Noor-ul-Ane et al, 2018). In addition, a nulceopolyhedrovirus has been isolated that is selective to H. armigera (HaNPV), and is a safe and effective alternative to insecticides (Cherry et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has shown that HaNPV can be used successfully to control H. armigera on various crops, including citrus (Moore et al, 2004) and chickpea (Moshtaghi-Maleki et al, 2014;Ojha et al, 2017). The gregarious ectoparasitoid wasp Habrobracon hebetor Say (Hymenoptera: Braconidae) is an effective larval parasitoid of H. armigera (Noor-ul-Ane et al, 2018). Because both entomopathogenic agents are most active against early-instar caterpillars (Pourmirza, 2000;Magholi et al, 2014;Sedaratian et al, 2014), and H. hebetor preferentially parasitizes later instars, the combined use of these agents could potentially result in additive mortality of larval stages and provide an effective and safe solution for H. armigera management on chickpea.…”
Section: Introductionmentioning
confidence: 99%